Phase-field investigation on the growth orientation angle of aluminum carbide with a needle-like structure at the surface of graphite particles. (7th June 2019) - Cai, Yuhan; Wang, Fei; Selzer, Michael; Nestler, Britta
Abstract: We adopt a phase-field model for peritecitc phase transition to investigate the critical orientation angle of a needle-like Al4 C3 structure on the surface of graphite. The critical orientation angle is defined as the maximum angle for which the Al4 C3 particle can grow. A crystalline (facetted) anisotropy is exploited to depict the formation of the needle-like morphology. While the classical nucleation theory addresses the critical radius for crystal growth, it is still challenging to determine the critical orientation angle when strong anisotropy is involved. For a single Al4 C3 particle, we explore the effect of the basis radius of the graphite and the particle size on the critical orientation angle. For two adjacent Al4 C3 particles, we rationalize the critical orientation angle with the apart distance, the radius and the individual orientation of the particle. Depending on the geometric configuration, we observe three typical competing effects which determine the critical orientations differing from a single Al4 C3 particle. We anticipate that the simulation results can be applied to interpret some microstructural evolutions with strong anisotropies.